Urban traditions and historic environments in Sindh - Naeem, Anila, author. Link Link
1 online resource (266 pages)
Keywords: Shikarpoor Historic City, in Sindh, Pakistan, has a rich historical heritage: as a central point on caravan trade routes, it served as the gateway to Afghanistan and Central Asia. In recognition of that history, in 1998 the government of Sindh named it a protected heritage site-but that status hasn't prevented the ongoing destruction of the city's historic fabric. This book tells the story of Shikarpoor and presents as complete a picture of its threatened historical fabric as possible, through copious maps and images past and present.